Problematika Kurikulum dan Pembelajaran Pendidikan Karakter - Julaeha, Siti (Jurnal Penelitian Pendidikan Islam, 2019)
Curriculum plays an important role in realizing future generations that are useful for the nation and state. Who has the nature of responsibility, creative, innovative, and become an expert. The curriculum is the heart of a school and the school is the heart of society and the society is the heart of the nation. So that the nation will advance if it has high quality and high quality of human resources. However, curriculum development often finds many problems that require consideration and solution from the discussion of definitions, scope, characteristics, principles, objectives, concepts, as well as curriculum development and as well as learning and character education which are emphasized in the national curriculum. The understanding of character, components, elements, goals, functions, principles, character values, methods of character education concepts, to curriculum problems and character education learning is so important for us to understand.